PENGARUH MODEL PEMBELAJARAN DISKURSUS MULTI REPRESENTASI (DMR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA UPTD SMP NEGERI 7 GUNUNGSITOLI - Nurul Ihsani Giawa; Yakin Niat Telaumbanua; Sadiana Lase; Ratna Natalia Mendrofa (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study is based on the results of a preliminary study conducted by researchers at UPTD SMP Negeri 7 Gunungsitoli, found problems, namely (1) the learning model in the classroom is less varied and (2) the lack of students' mathematical problemsolving abilities in solving mathematical problems. The purpose of this study was to determine the effect of the Multi Representation Discourse (DMR) learning model on the mathematical problemsolving abilities of students at UPTD SMP Negeri 7 Gunungsitoli. This type of research is quantitative research using a quasiexperimental method with a pretest-posttest control group design. The population of this study was grade VIII students and the research sample consisted of two classes, namely VIII-C as the experimental class and VIII-A as the control class. The instrument in this study was in the form of a mathematical problemsolving ability essay test. The results of the study obtained based on oneparty hypothesis testing obtained a tcount value = 5,283 and a ttable value = 1.678. Because tcount > ttable or 5,283> 1.678, reject H0 and accept Ha, which means "there is an influence of the Multi Representation Discourse (DMR) learning model on students' mathematical problemsolving abilities".